La exhibición y el merchandising en las tiendas de barrio de Bogotá: un canal que cobra fuerza como oportunidad para la construcción de marca (2013)
Convenience stores in Colombia as distribution channels still have opportunities for growth in some categories, since they are a tool for attracting capital, job opportunities and support to the domestic industry by providing easy access to products and good prices and closer interpersonal relationships between shopkeeper and consumer. On the contrary, it is not evidenced in a supermarket store, which despite its emergence and growth could not remove the already established neighborhood ties, even when the end of the neighborhood store was predicted with the emergence of big supermarket chains like Jumbo, Éxito and Makro. Factors such as location, friendliness, credit to their customers (virtual wallet), miniaturizing of products and good prices and personal contact with the client; has helped convenience stores to maintain a strong economic, cultural and commercial lead in Bogotá.